From Digital Technology to Society: Algospeak and Communication Styles on Social Media in The Era of Artificial Intelligence (AI) - Isam, Hishamudin (Proceeding of International Joint Conference on UNESA, 2025)
In the era of artificial intelligence (AI), digital technology has revolutionized how society communicates, especially on social media platforms. A notable emerging phenomenon is algospeak, which involves the use of modified language to avoid censorship by platform algorithms, such as those on TikTok and Instagram. Algospeak enables users to discuss sensitive topics like mental health or political issues without facing restrictions. This phenomenon illustrates how users adapt to the strict regulations imposed by digital technology. However, algospeak presents a dilemma regarding the accurate transmission of information. The use of veiled language can lead to misunderstandings among users who are unfamiliar with specific codes, complicating clear communication. This situation challenges the balance between censorship and freedom of expression in the digital realm. In this context, linguists have a vital role in analyzing the evolution of algospeak and collaborating with platform operators to develop algorithms that better understand language context and nuances. With a more inclusive approach, linguists can help social media platforms create systems that not only filter inappropriate content but also preserve openness in communication. Ultimately, algospeak reflects users’ linguistic creativity in adapting to digital technology, offering both challenges and opportunities for enhancing the online communication ecosystem in this AIdriven era.